Nitroblue Tetrazolium Reduction by Neutrophils in Experimental Hemorrhagic Shock - Hallett, John W. (1973)
This study was designed to ascertain the effect of prolonged hemorrhagic hypotention on nitroblue tetrazolium (NBT) reduction by neutrophils and, consequently, to determine whether the qualitative NBT test is a reliable aid to rapid detection of systemic bacterial infection and endotoxemia after severe hemorrhage. Nitroblue tetrazolium reduction by neutrophils did not appear significantly altered by 2 hours of hemorrhagic hypotension in dogs, but moderate increase in NBT-positive neutrophils was observed after the reinfusion of shed blood. More importantly, leukocytes from shock blood did increase NBT reduction under endotoxin stimulation. These findings imply that the NBT test is a reliable indicator of systemic bacteria and endotoxin prior to resuscitation with stored blood, but in the immediate postreinfusion period, increased NBT metabolism in phagocytic leukocytes may represent either systemic bacterial invasion or neutrophil damage secondary to blood storage and in vivo metabolic derangements associated with shock.